Development Of Carbonated Hydroxyapatite/ Poly(L-Lactide)/ Poly(Vinyl Alcohol) Biocomposites - Kee, Chia Ching (2013)
Nanosized B-type carbonated hydroxyapatite (CHA) was successfully synthesized through nanoemulsion method, by both dropwise (DW) and direct pouring (DP) techniques. The CHA powders obtained by DP method contained higher CO3 2- content with smaller near-spherical size, as compared to the one by DW with elongated shape. Moreover, the CHA particle size was found to decrease with increasing CO3 2- content, with maximum CO3 2- substitution of 14 wt%. Annealing followed by carbonation at cooling stage on CHA was carried out in the range of 300 900 °C. The optimum temperature of 700°C was determined from the adequate B-type CO3 2- content retained and improved crystallinity of the annealed powder. In the biocomposite fabrication of CHA with poly(L-lactide) (PLLA) and/or poly(vinyl alcohol) (PVA), hydrogen bonding was deduced to form between hydroxyl group of CHA and carbonyl of PLLA, while no interaction was observed between CHA with PVA. When CHA/PLLA/PVA biocomposites were fabricated, PLLA served as coupling agent which bridged CHA and PVA via hydrogen bonding. From the mechanical aspect, diametral tensile strength (DTS) of the biocomposites was found to increase with increasing polymer loading and when PLLA was added instead of PVA. Nevertheless, CHA/PLLA/PVA biocomposites exhibited comparable DTS value at lower polymer content. In terms of bioactivity, the CHA/PLLA/PVA biocomposite showed better resorption rate and apatite formation as compared to CHA/PLLA, while CHA/PVA was low with highest weight loss in simulated body fluid.